2014
DOI: 10.5114/pm.2014.45002
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: a family at risk

Abstract: The diagnosis of cancer is a family experience that changes the lives of all its members, bringing an immense amount of stress and many challenging situations. The daily routine, common activities and distribution of duties all have to change. Family members follow the phases of the disease, very often suffering comparable or greater distress than the patient. They use various coping methods which aim at helping both the sick relative and themselves. These methods, together with emotional responses, change ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 53 publications
4
67
0
7
Order By: Relevance
“…Availability or access to a hardship fund could perhaps alleviate some of the financial pressure for caregivers. A finding that also concurred with that of Woźniak & Iżycki [35] who reported that home palliative caregivers develop economic difficulty because of their caregiving responsibility.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Availability or access to a hardship fund could perhaps alleviate some of the financial pressure for caregivers. A finding that also concurred with that of Woźniak & Iżycki [35] who reported that home palliative caregivers develop economic difficulty because of their caregiving responsibility.…”
Section: Discussionsupporting
confidence: 74%
“…A finding that relates to caregivers lack of preparedness and feelings of fear, anxiety, stress, inadequacy and uncertainty about their ability of providing home care. [20,[35][36][37][38][39] Furthermore, the literature affirmed that there was no discussion about what to expect in palliative home care and carers felt health professionals were hesitant to discuss difficult issues like managing palliative care at home and end of life care. [40] Thus, they learned caregiving skills by trial and error.…”
Section: Discussionmentioning
confidence: 99%
“…Target compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were obtained in a three step reaction procedure (Scheme 1). First step involves the synthesis of 1-(2-chlorobenzyl)-3-phenylthiourea (3) by the reaction of 2-chlorobenzylamine (1) and phenyl isothiocyanate (2) in toluene at room temperature. In the second step, anhydrous sodium acetate assisted cyclization of (3) in absolute ethanol and chloroacetic acid yielded 3-(2chlorobenzyl)-2-(phenylimino)-1,3-thiazolidin-4-one (4).…”
Section: Resultsmentioning
confidence: 99%
“…There is less known about how the rest of the family supports the member with cancer. Woźniak and Iżycki (2014) concluded that other family members' perspective has not been given enough attention in this context. Furthermore, Coyne, Dieperink, Østergaard and Creedy (2017) have argued that little attention has been given to the resources the family offers to their kin with cancer, particularly whether the support is influenced by differences in settings or cultures.…”
Section: Present Studymentioning
confidence: 99%